Can Clay Mimic the High Reflectivity of Briny Water Below the Martian SPLD?. Issue 3 (28th February 2023) - Cosciotti, Barbara; Mattei, Elisabetta; Brin, Alessandro; Lauro, Sebastian Emanuel; Stillman, David E.; Cunje, Alister; Hickson, Dylan; Caprarelli, Graziella; Pettinelli, Elena
Abstract: It has recently been suggested that clay minerals, which are widespread on the Martian surface, could be the possible source of the basal bright reflections detected by MARSIS at Ultimi Scopuli, instead of briny water. This hypothesis is based on dielectric measurements on a wet Ca‐Montorillonite (STx‐1b) sample conducted at 230 K, which reported permittivity values (apparent permittivity of 39 at 4 MHz) compatible with the median value of 33 retrieved by MARSIS 4 MHz data inversion in the high reflectivity area. These experimental results are, however, incompatible with well‐established dielectric theory and with laboratory measurements on clays, at MARSIS frequency and Martian temperatures, reported in the literature. Here, we replicate the experiment using a setup to precisely control the rate of cooling/warming and the temperature inside and outside the clay sample. We found that the rate of cooling, the position of the temperature sensor and, consequently, the thermal equilibrium between the sample and the sensor play a fundamental role in the reliability of the measurements. Our results indicate that even for a large water content in the clay sample, at 230 K and 4 MHz, the apparent permittivity is only 8.4, dropping to 4.1 at 200 K, ruling out clays as a possible source of the bright reflections detected by MARSIS at the base of the SPLD. Plain Language Summary: The recent discovery of bright basal reflections below the South polar ice cap at Ultimi Scopuli (Mars) by MARSIS has sparked an intense debate on their origin. Because bright radar reflections detected below the ice sheets in Antarctica and Greenland usually indicate the presence of basal water, and based on additional data processing methods, these anomalies were interpreted to be caused by liquid briny water. Recent laboratory measurements questioned this hypothesis and instead suggested that the presence of clay could explain the observed results. According to these measurements, the dielectric properties of wet clay at 230 K (−43°C) mimic the high reflectivity of briny water. Here, we replicate the experiment, making sure to reach thermal equilibrium during each measurement run to guarantee that the temperature is correctly evaluated when the dielectric properties of the sample are measured. This was accomplished using a dedicated setup to precisely control the thermal cycle and to carefully check the internal and external temperatures of the wet clay sample. Our experimental results clearly show that the dielectric properties of clay at 230 K are incompatible with the observed MARSIS anomalies and thus briny water remains the most plausible explanation for the bright basal reflections detected by MARSIS. Key Points: Anomalous bright basal reflections have been detected by MARSIS at Ultimi Scopuli, Mars Dielectric measurements of wet clays at low temperature show that they cannot generate strong basal reflections Reliable measurements of dielectric behavior of planetary analogs require a careful control of the temperature inside the sample